Have yourself a Goofy little Christmas - Taylor, Robert, 1944-2014; Magon, Jymn; Cartwright, Nancy, 1959-; Cummings, Jim, 1952-; Farmer, Bill, 1952-; Hill, Dana, 1964-1996; Paulsen, Rob, 1956-; Welker, Frank; Winchell, April; Walt Disney Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) ([United States] : Walt Disney Studios Home Entertainment, 2014)
Big-hearted Goofy pulls out all stops for his son Max on Christmas. The problem is, he also shorts out the neighborhoods electricity and usually blows up his house in the process!
Title from title screens.
Voices: Bill Farmer, Dana Hill, Nancy Cartwright, Jim Cummings, Rob Paulsen, Frank Welker, April Winchell.
Rating: Not rated. CHV rating: G.
DVD, region 1; full screen (1.33:1) presentation; Dolby Digital stereo; digitally mastered; dual-layer; NTSC.
English subtitles for the deaf and hard-of-hearing.
105837
Keywords: Goofy -- (Fictitious character) -- Juvenile films; Christmas -- Juvenile films; Films for the hearing impaired; Animated films; Children's films; Christmas films; Fiction films; Juvenile works